JOINT VENTURE VS. WHOLLY OWNED SUBSIDIARY: STRATEGIC ADAPTATION OF TOYOTA MOTOR CORPORATION - Hidayatullah, Achmad Fatkhu Rochim; Novica, Diah Ayu (Universitas Islam Malang, 2024)
This study aims to analyze Toyota Motor Corporation's international expansion strategy by comparing two main approaches: Joint Venture (JV) and Wholly Owned Subsidiary (WOS). This comparative case study is conducted in the context of China and the United States, two key markets with distinct institutional and regulatory characteristics. Using a qualitative approach and secondary data analysis, the study finds that Toyota chooses the JV strategy in markets with high regulatory barriers to gain legitimacy and local access, while WOS is used in stable markets to maintain full control and protect innovation. These findings are analyzed through the lens of Transaction Cost Theory and Institutional Theory, which explain that strategic choices are not solely based on internal efficiency but also adaptation to institutional pressures. The results of this study provide theoretical contributions to the study of internationalization strategies and practical implications for multinational companies in designing contextual and sustainable market entry strategies.